A 65‐nm 28‐GHz CMOS Wilkinson power divider with improved isolation. Issue 4 (6th February 2022) - Song, Jae‐Hyeok; Oh, Hyun‐Myung; Kim, Choul‐Young
Abstract: In this study, we implemented a Wilkinson power divider/combiner composed of lumped elements suitable for 28‐GHz of fifth‐generation mobile communication technology. To improve the isolation of the system, signal perfect cancellation analysis is used with optimized values of the lumped elements of the Wilkinson power divider, which is fabricated using bulk complementary metal–oxide–semiconductor (CMOS) 1P9M 65‐nm process and the fabricated circuit area was 0.046 mm 2 . The measured insertion loss of this system is less than 0.62 dB, input/output matching exceeds 16.9 dB, and isolation between the output ports exceeds 19.6 dB in the operating frequency range of 25.5–29.5 GHz. The circuit thus has low insertion loss and good isolation compared to conventional Wilkinson power dividers manufactured for use in the similar frequency bands.